Registro de Leptocybe invasa no estado de Goiás - Pereira, Jaqueline Magalhães; Melo, Aniela Pilar Campos de; Rodrigues, Ohana Daroszewki; Dias, Thaíse Karla Ribeiro [UNESP]; Wilcken, Carlos Frederico [UNESP] (Universidade Federal de Santa Maria, 2014)
The first occurrence record of Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae) in Goias state in Eucalyptus grandis Hill ex Maiden. The detection occurred in the county of Goiânia, Brazil.

Registra-se a primeira ocorrência de Leptocybe invasa Fisher & La Salle (Hymenoptera: Eulophidae) no estado de Goiás em Eucalyptus grandis Hill ex Maiden. A detecção ocorreu no município de Goiânia.
Record of the Leptocybe invasa in the state Goiás, Brazil
Keywords: gall wasp; forestry pest; Eucalyptus spp.; vespa-de-galha; praga florestal; Eucalyptus spp.